INFILTRATION CAPACITY DERIVATIVES AND SOIL MOISTURE EQUATION MODEL VALIDATION - Martheana Kencanawati; Data Iranata; Mahendra Andiek Maulana; A. A. Ngurah Satria Damarnegara (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2024)
Infiltration is an essential parameter in runoff, although its simulation remains challenging due to soil heterogeneity and complex structures. As soil moisture increases, infiltration capacity decreases nonlinearly, stabilizing when saturation is reached. Therefore, this study aimed to improve and validate the Horton Equation using field observations to determine infiltration capacity in watersheds. Overland flow observations were used to assess simulation accuracy from the previous studies, the sensitivity curve number was obtained at a range of 49–57. The results showed that high precipitation saturated initial losses and infiltration capacity, producing a greater runoff coefficient. The sensitivity curve numbers were obtained differently between Pandantoyo sub-basin (CN 49–53) and Ngadirejo sub-basin (CN 53–55). From modification runoff coefficient values (dimensionless,) for an ungauged catchment, it could be obtained function of f (R24, Sm), LU. Soil moisture value between Pandantoyo and Ngadirejo sub-basin was 3,562. It was also discovered that C was Q from AWLR observation and time of concentration, which influenced water discharge. A longer Tc led to lower discharge without increasing water levels. Furthermore, SCS Direct runoff method had minimal impact on runoff coefficients.